A rare variant of extraskeletal osteosarcoma presenting as a clinically benign subcutaneous neoplasm. (1st May 2019) - Ryan, Michael P.; Woolridge, Katelyn F.; Sedrak, Michael; Berlingeri‐Ramos, Alma C.; Group, Ashley R.
Abstract: Extraskeletal osteosarcoma (ESOS) is a rare variant of osteosarcoma that arises without attachment to the underlying skeleton. These cancers are typically found embedded in deeper tissues, most commonly the muscle or fascia, and are rarely found within the skin or subcutis. Most tumors are large in size upon initial presentation, and carry a poor prognosis. We discuss the case of a 48‐year‐old Caucasian woman who presented to a dermatology clinic with an asymptomatic, small, mobile, subcutaneous mass that appeared clinically benign. After elective removal and histopathologic examination, the patient was diagnosed with ESOS. ESOS presenting in this manner is exceedingly rare, and this case highlights the importance of sending all excised specimens, even those with a benign presentation, for pathologic examination.